Preempting plantparasitic nematode losses on banana in Africa: which species do we target? - Coyne, Danny L. (2009)
Plant-parasitic nematodes cause serious damage on banana in Africa. Affected plants are less able to access nutrients and water, leading to yield losses, particularly under nutrient- and water-stressed conditions. Heavily affected plants often topple, with consequent total loss of bunches, while plantation longevity is drastically reduced. The problem is exacerbated by the use of nematode-infected planting material that results in the movement of nematodes to new fields. Promotion of the use of healthy planting material is a first step towards management of nematode problems in banana, and nematode-resistant cultivars are important complementary options. Radopholus similis has traditionally been presumed to be the most important nematode on banana and is the target of breeding programmes. Although this belief may once have been accurate in Africa, and in some circumstances remains relevant, recent surveys have shown an increasing incidence of Pratylenchus coffeae, particularly in West Africa where it can be the most important species. Other species are also involved, most often in combination with P. coffeae. Little is known about the distribution of nematodes and their relative importance on banana for many areas in Africa. However, available information indicates that breeding programmes should take into consideration more than R. similis, since resistance against it does not necessarily provide resistance against other species. Furthermore, ‘resistant’ cultivars can react differently to different strains or pathotypes of the same nematode species. Addressing the nematode problem in Africa is dependant on increasing farmers’ awareness to, and the promotion of, the use of healthy planting material. The development of resistant cultivars will undoubtedly support the management of nematodes, but accurate diagnostic and epidemiological information is also required.